Biogenic synthesis of copper oxide nanoparticles using Eucalyptus globulus Leaf Extract and its impact on germination and Phytochemical composition of Lactuca sativa - Sadaf Anwaar; Faiza Altaf; Tauseef Anwar; Huma Qureshi; Ejaz Hussain Siddiqi; Walid Soufan; Wajid Zaman (Scientific Reports)
Abstract Green nanomaterials are increasingly used to improve plant growth and phytochemical traits. This study employed Eucalyptus globulus leaf extract, a medicinal plant, as a bio-reductant and capping agent to synthesize copper oxide nanoparticles (CuO-NPs), which were applied as seed primers for Lactuca sativa (lettuce), an annual species prized for its short germination time and rich bioactive compounds. Characterization of CuO-NPs using FTIR, XRD, SEM, and EDX confirmed their purity, crystalline structure, and an average particle size of 74.66 nm. The CuO-NPs were applied at concentrations of 0.01 mg/ml, 0.02 mg/ml, 0.03 mg/ml, and 0.04 mg/ml. At the highest concentration (0.04 mg/ml), significant reductions in physical growth parameters were observed, with plant length, height, and width measuring 7.85 cm, 5.50 cm, and 3.48 cm, respectively, compared to 13.70 cm, 11.52 cm, and 11.18 cm in control plants. Phytochemical analysis identified tannins, alkaloids, phytosterols, saponins, flavonoids, and glycosides in all methanolic extracts, while carotenoids were absent at higher concentrations (0.03 mg/ml and 0.04 mg/ml) due to phytotoxicity. FTIR analysis revealed a prominent peak at 858 cm⁻¹ at 0.01 mg/ml, indicating the presence of antioxidant-rich aromatic phenyl compounds. In conclusion, the study demonstrates that CuO-NPs synthesized using Eucalyptus globulus extract enhance phytochemical constituents at optimal concentrations but inhibit growth and reduce key phytochemicals at higher doses. Future research should optimize nanoparticle concentrations to minimize phytotoxicity while maximizing beneficial effects on plant growth and bioactive compounds.